Discerning justice: clarifying the role of procedural and interactional justice in restorative conferencing. Issue 1 (2nd January 2021) - Scheuerman, Heather L.; Gilbert, Talia N.; Keith, Shelley; Hegtvedt, Karen A.
ABSTRACT: Research suggests that offenders perceive restorative justice (RJ) conferences as more just and reintegrative than standard court proceedings. Yet, little research focuses on how the nature of the offense may affect these social psychological processes, and studies that investigate how offenders perceive justice typically examine justice in general, not specific types (procedural vs. interactional). Using data from the Australian Reintegrative Shaming Experiments (RISE), we find that offense type is differentially associated with types of justice and shaming perceptions, demonstrating the need to distinguish between interactional and procedural justice to understand how various offenders experience the RJ conference.